Prowadzenie działalności rolniczej na obszarach „Natura 2000" - aspekty prawne - Otawski, Piotr (Wydawnictwo Naukowe UAM, 2007)
Agricultural activity is the most common way in which man may influence the environment in areas designated as parts of “Natura 2000” network. Therefore, appropriate rules regulating agricultural activity within the European ecological network “Natura 2000” create an imperative condition for the success of the European project which aims at conservation of the natural resources on the European continent. The paper is an attempt to analyse and evaluate that part of Polish legislation which should provide for legal protection of habitats and species in special areas of conservation and special protection areas, as well as secure a system of financial support for the types of agricultural activity that are recommended for those areas.
ENGAGING IN AGRICULTURAL ACTIVITIES IN THE "NATURA 2000" AREAS - LEGAL ASPECTS